Characterization of Five Transmembrane Proteins: With Focus on the Tweety, Sideroflexin, and YIP1 Domain Families - Attwood, Misty M.; Schiöth, Helgi B. (Frontiers in Cell and Developmental Biology, 2021)
Transmembrane proteins are involved in many essential cell processes such as signal transduction, transport, and protein trafficking, and hence many are implicated in different disease pathways. Further, as the structure and function of proteins are correlated, investigating a group of proteins with the same tertiary structure, i.e. the same number of transmembrane regions, may give understanding about their functional roles and potential as therapeutic targets. This analysis investigates the previously unstudied group of proteins with five transmembrane-spanning regions (5TM). More than half of the 58 proteins identified with the 5TM architecture belong to twelve families with two or more members. Interestingly, more than half the proteins in the dataset function in localization activities through movement or tethering of cell components and more than one-third are involved in transport activities, particularly in the mitochondria. Surprisingly, no receptor activity was identified within this dataset in large contrast with other TM groups. The three major 5TM families, which comprise nearly 30% of the dataset, include the tweety family, the sideroflexin family and the Yip1 domain (YIPF) family. We also analyzed the evolutionary origin of these three families. The YIPF family appears to be the most ancient with presence in bacteria and archaea, while the tweety and sideroflexin families are first found in eukaryotes. We found no evidence of common decent for these three families. About 30% of the 5TM proteins have prominent expression in the brain, liver, or testis. Importantly, 60% of these proteins are identified as cancer prognostic markers, where they are associated with clinical outcomes of various tumor types. Nearly 10% of the 5TMs are still not fully characterized and further investigation of their functional activities and expression is warranted. This study provides the first comprehensive analysis of proteins with the 5TM architecture, providing details of their unique characteristics.